1990
DOI: 10.1128/aac.34.10.1921
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue penetration of a single dose of ornidazole (1,000 milligrams intravenously) for antibiotic prophylaxis in colorectal surgery

Abstract: Levels in serum and tissue penetration of ornidazole were studied after a single intravenous injection of 1,000 mg given to 14 patients for prophylaxis of surgical infection. They were scheduled for elective colorectal surgery. Adequate levels in blood (2MIC for 90% of Bacteroides fragilis strains tested) were found in all patients throughout the procedure and up to hour 24. Mean-maximal (15 min) and last-determined (24 h) ornidazole levels in serum were 24 5.2 and 6.3 1.4 mg/liter, respectively. 13-Phase elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…The penetration rates found in the present study are similar to those described in other studies during classical gut surgery (12). However, our results might also take into account the fact that perioperative conditions during liver transplantation may modify blood and/or tissue drug concentrations.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The penetration rates found in the present study are similar to those described in other studies during classical gut surgery (12). However, our results might also take into account the fact that perioperative conditions during liver transplantation may modify blood and/or tissue drug concentrations.…”
Section: Resultssupporting
confidence: 80%
“…These drugs were chosen because of their known pharmacokinetic properties and their spectra of activity (3,12,16). Plasma and epiploic fat drug concentrations were determined until the end of the surgical procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The penetration into fatty tissue relative to drug concentrations in serum was estimated to be from 10 to 13% in the study patients (Table 1). In another study performed under similar clinical conditions, ornidazole demonstrated a higher tissue penetration into fatty tissue (from 23 to 26%) and 84 to 100% of patients had ornidazole levels in tissue >MICgo for B. fragilis (15). What constitutes optimal tissue levels of antibiotics is poorly understood (2).…”
Section: Resultsmentioning
confidence: 99%
“…The metronidazole levels in serum and pharmacokinetic parameters of the study patients were as follows: maximum level (at 15 (1,10,20), and the main points are as follows. (i) The antimicrobial agent must be present in the involved tissues before surgery allows bacterial contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have shown that the maximal plasma concentration of the therapeutic dose (121.5 g/d) of ornidazole was around 100 mM (Martin et al, 1990;Li et al, 2002;Wang et al, 2008;Wei et al, 2010). Therefore, the UGT isoform screening experiment was conducted at 100 mM and higher substrate concentrations (1 and 50 mM), in case of missing isoforms with low affinity.…”
Section: Discussionmentioning
confidence: 99%